1978
DOI: 10.1083/jcb.79.2.342
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and extracellular deposition of fibronectin in chondrocyte cultures. Response to the removal of extracellular cartilage matrix.

Abstract: Fibronectin, the major cell surface glycoprotein of fibroblasts, is absent from differentiated cartilage matrix and chondrocytes in situ. However, dissociation of embryonic chick sternal cartilage with collagenase and trypsin, followed by inoculation in vitro reinitiates fibronectin synthesis by chondrocytes. Immunofluorescence microscopy with antibodies prepared against plasma fibronectin (cold insoluble globulin [CIG]) reveals fibronectin associated with the chondrocyte surface. Synthesis and secretion of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
96
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 210 publications
(97 citation statements)
references
References 35 publications
1
96
0
Order By: Relevance
“…No extracellular type II collagen matrix is observed during the first days in monolayer culture when cells have flattened, as demonstrated previously (5,29,32) . It is unlikely that the failure of extracellular deposition of type II collagen in early stages of the culture resulted from lack of ascorbate (8,24), for fresh sodium ascorbate was added with each medium change.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…No extracellular type II collagen matrix is observed during the first days in monolayer culture when cells have flattened, as demonstrated previously (5,29,32) . It is unlikely that the failure of extracellular deposition of type II collagen in early stages of the culture resulted from lack of ascorbate (8,24), for fresh sodium ascorbate was added with each medium change.…”
Section: Discussionmentioning
confidence: 48%
“…Type II collagen reappears in the extracellular space after chondrocytes in the center of epithelioid colonies reassume spherical shape and accumulate highly refractile extracellular matrix (5) . This matrix stains with antibodies to both CSPG and type II collagen (Fig.…”
Section: Deposition Of Extracellular Type 11 Collagen In Well-differementioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemical and clectronmicroscopical studies on isolated chondrocytes (15)(16)(17)(18)(19) have demonstrated a close association of type II collagen with the chondrocyte surface . The precise nature ofthis cell:matrix association, however, is still unclear .…”
mentioning
confidence: 99%